Validation and correlations of the Angioedema Activity Score (AAS), Angioedema Quality of Life (AE-QoL) questionnaire, and Angioedema Control Test (AECT) in Chinese patients with angioedema - Hugo W.F. Mak, MBBS; Jane C.Y. Wong, MBBS; Sophia W.M. So, MBBS; Dorothy L.Y. Lam, MSc; Karsten Weller, MD; Marcus Maurer, MD; Philip H. Li, MBBS, MD (Journal of Allergy and Clinical Immunology: Global, 2024)
Background: The impact of recurrent angioedema can be severely debilitating and remains difficult to quantify. Several standardized patient-reported outcome measures (PROMs), including the Angioedema Activity Score (AAS), Angioedema Quality of Life (AE-QoL) questionnaire, and Angioedema Control Test (AECT), have been developed and translated into different languages. However, these PROMs have yet to be validated in Chinese individuals, and their correlations in the Chinese population remain unknown. Objective: Our aim was to validate the Chinese versions of the AAS, AE-QoL questionnaire, and AECT and assess their intercorrelations. Methods: A prospective cohort of 118 Chinese patients with recurrent angioedema at the Angioedema and Urticaria Centre of Reference and Excellence in Hong Kong completed the traditional Chinese versions of the AAS, AE-QoL questionnaire, and AECT. We analyzed the reliability and validity of these PROMs and their correlations with each other as well as with generic PROMs. Results: The Chinese AAS, AE-QoL questionnaire, and AECT demonstrated excellent internal consistency (Cronbach α = 0.920, 0.976, and 0.832, respectively; McDonald ω = 0.972, 0.977, and 0.901, respectively). Confirmatory factor analysis for the AE-QoL questionnaire showed an acceptable fit with the 4-dimensional model (comparative fit index = 0.869; Tucker-Lewis index = 0.842). The AECT showed significant correlations with both the AAS and AE-QoL questionnaire (ρ = –0.750 and –0.456 respectively [both P < .05]). The AE-QoL questionnaire was moderately correlated with certain domains of generic PROMs such as the Work Productivity and Activity Impairment Questionnaire: General Health, version 2.0, and the Short Form 12-Item Health Survey, version 2 (all ρ < 0.60). Conclusion: The Chinese AE-QoL questionnaire, AAS, and AECT are valid and reliable tools for use with Chinese patients. More validated tools should be made available to improve patient care and research for all patients with angioedema globally.